A formação de padres na diocese de São Carlos - Rossi, Renan (Universidade Federal de São Carlos, 2015)
Trying to understand a process through which individuals are raised in certain skills and dispositions, "physical and moral states" that are required by society as a whole, but also by specified groups to which one belongs, I conducted a research about the formation of Catholic priests process. I tried to understand from the experience of the diocese of São Carlos / SP, which dynamic, actors and situations were involved in this process of socialization, through which are cultivated in seminarians a number of provisions that in the future will contribute to the exercise of their priestly ministry. This set of provisions that I call priestly habitus is unconsciously and sometimes deliberately instrumentalized by these social actors, both in the daily performance of their social roles and in the maintenance activity or achievement of social positions in the Catholic Church or even in other fields such as the academic one. The dynamics of such priestly habitus cultivation takes place in a broad context, larger than the boundaries of a seminary, covering a range of training situations arranged through an institutionalized itinerary experiences that culminates in ordination. Such a priestly itinerary - equipped with native significance through a structured vocational speech that reduces the importance of profane motivations in the admission at the seminary provides the trajectories of these actors with a purity of inclination that omits the possibility of other interests (less transcendental ones). Finally, I discuss how to some members of the Catholic clergy, to be a priest not as regarded in the official speeches, but in the daily practices is less of an inescapable fixed identity than a contingency identification activity, which is evoked or omitted by these social actors according to the nature of relations at stake.
Keywords: Socialização; Seminários teológicos católicos; Formação presbiteral; Habitus sacerdotal; Igreja Católica; Socialization; Catholic seminaries; Priestly education; Sacerdotal habitus; Catholic Church; CIENCIAS HUMANAS::SOCIOLOGIA